The impacts of suspended mariculture on coastal zones in China and the scope for Integrated Multi-Trophic Aquaculture - Reece Wartenberg (Taylor & Francis Group, 2017)
Introduction: China is responsible for more than 60% of global aquaculture production. As the frontiers of food production have expanded, the cultivation of marine organisms in coastal zones and the open ocean has grown rapidly. The dominant mariculture industry in China is suspended mariculture, which uses net cages, ropes, or other structures suspended in the water column to cultivate aquatic organisms. This systematic, quantitative review provides a clear and comprehensive account of research that has investigated the adverse impacts of suspended mariculture in China and reviews research that has applied Integrated Multi-Trophic Aquaculture (IMTA) systems for mitigating impacts. This work builds on 218 peer reviewed papers that have been published in English-language journals. Outcomes: Eighteen impacts were identified, including chemical, ecological, physical, and socioeconomic impacts. Eighteen measures for improving suspended mariculture were recommended consisting of government department, farm management, and ecological engineering measures. IMTA was the most frequently recommended measure. The capabilities of IMTA for bioremediation and increased farm production were the most frequently studied advantages. Seven other benefits have been explored but remain understudied. The current challenges facing the expansion of commercial IMTA include limited use of new technology, limited skills development, decreasing production of low trophic-level species, biogeographic and temporal barriers, and negative system feedbacks. Conclusion: Despite challenges, implementing commercial IMTA is a promising measure for reducing the impacts of suspended mariculture because it presents a range of secondary benefits that can improve the overall sustainability of aquaculture in the coastal zone.